MOTIVASI BELAJAR SISWA DALAM PENINGKATAN KETERAMPILAN MEMBACA AL-QUR’AN PESERTA DIDIK MAN I TIDORE - Muhaajirah, Misbahul; Shunhaji, Akhmad; Nawawi, Abd Muid (PMPP Lembaga Penelitian dan Studi Kebijakan, 2024)
This research aims to describe improving the Al-Qur'an reading skills of MAN 1 Tidore students through student learning motivation. This research uses a survey method with interviews, observation and documentation. The results of this research show that the Al-Qur'an reading skills of students at MAN 1 Tidore that a person must master when learning the Al-Qur'an include: tartil, recitations and fluent qiro'at. So the process of learning to read and write the Qur'an is related to reading skills by presenting several levels or possession of adequate mastery of tajwid knowledge, in terms of makhorijul letters, shifatul letters, ahkamul letters, ahkamul mad wal qasr, ahkamul waqaf wal ibtida. The general situation/picture regarding student learning motivation at MAN I Tidore has improved with the implementation of collaboration between student guardians, class teachers, teaching teachers through tutoring services planned by teaching teachers as student supervisors at MAN 1 Tidore. With this form of tutoring service, students are given knowledge, coached and guided to become knowledgeable students with morals. Efforts to improve Al-Qur'an reading skills through learning motivation at MAN 1 Tidore, namely through habituation, giving grades or prizes, communication carried out on both sides, between the ustadz and parents, and providing guidance